Millennials’ Online Purchase Intention Towards Consumer Electronics : Empirical Evidence from India - Bulsara, Hemantkumar P.; Vaghela, Pratiksinh S. (Indian Journal of Marketing, 2022)
Millennials are those born between 1980 and 2000. They are the first digital generation of the 21st century. Millennials’ ability to see the world through the eyes of the digital lens makes them a unique customer segment. Millennials have a higher purchase capacity compared to their older cohorts. Millennials have become an essential category of customers for marketers compared to other cohorts. The article examined the influence of perceived risk, e-service quality, subjective norms, and trust in the context of online shopping for consumer electronics products by millennials. The conceptual model was developed based on the previous studies to achieve these objectives. Data were collected from 474 digital shoppers from Surat, Ahmedabad, and Vadodara cities of Gujarat. The relationships among the constructs were analyzed by using structural equation modeling. The study results indicated that trust, e-service quality, and subjective norms influenced millennials’ online shopping intention for consumer electronics products. The findings provide significant implications for online retailers to develop millennials’ customer acquisition and retention strategies.